Assessing water retention and correlation to climate conditions of five plant species in greywater treating green walls. (15th December 2019) - Prodanovic, Veljko; Wang, Ankun; Deletic, Ana
Abstract: Green walls are becoming a popular infrastructure choice in densely built urban environments, due to their multiple benefits. However, high and vastly variable water requirements of these systems are preventing their further widespread. Only a small number of studies have investigated water needs of green walls, even though this can help to design more optimal systems with increased benefits. Additionally, the knowledge on interactions between plant uptake and climate conditions (temperature and humidity) is lacking. The aim of this study was to understand daily water requirements of five plant species ( C. appressa, N. obliterata, L. muscari, M. parvifolium and O. japonicus ) used in greywater treating green walls, across different seasons, temperature, and humidity conditions of temperate-oceanic climate (common in parts of Australia, US and Europe). The results showed that during summer, dominant water uptake processes were plant uptake and transpiration, resulting in three to four times higher water needs than during winter, when evaporation is a major effect. Top levels of the multi-level green wall exhibited significantly higher plant activity compared to bottom levels, showing four times greater water uptake. Temperature and humidity changes during winter caused the change in water uptake of plants, pointing to different growing and activity patterns of tested plants. During summer only N. obliterata showed temperature and humidity dependence. Annual plant water uptake and other practical recommendations are given based on the results. Even though this study focused on water requirements of greywater treating green walls, its findings can also inform traditional green wall designs. Graphical abstract: Image 1 Highlights: Green wall daily water needs vary from 4.3 L/m2 in summer to 0.5 L/m2 in winter. C. appressa the highest and O. japonicus the lowest water requirement plants. In summer dominant plant water uptake, while evaporation main process in winter. Only N. obliterata increased water uptake at temperatures above 27 °C. Plant position on green wall impacts water needs, with up to 75% used on top level.